Educational Game for Computational Thinking - Ismail, Asep Maulana; Nurjanah , Dade (Jurnal Locus Penelitian dan Pengabdian, 2025)
Computational Thinking (CT) is a fundamental problem-solving skill that encompasses analytical abilities to generate effective and efficient solutions. The core components of CT include decomposition, pattern recognition, abstraction, algorithms, and evaluation/debugging, with abstraction and decomposition serving as crucial foundational skills. The challenge of teaching CT in Indonesian schools stems from the shortage of teachers with adequate informatics competence, making innovative approaches such as necessary educative games. This study aims to develop and examine the effectiveness of an educational game based on a modified LightBot concept to train abstraction and decomposition skills among high school students who have never received CT instruction. The research method involved game design, implementation, and experimentation using a pre-test and post-test design. Data were analyzed descriptively to compare the improvement in CT skills between the experimental and control groups. The results showed a significant increase in CT scores, particularly in the abstraction and decomposition components, for the group using the educational game. Furthermore, the motivation survey indicated improved learning engagement in the experimental group. These findings strengthen the potential of educative games as an effective interactive learning medium for developing CT skills at the high school level.